1994
DOI: 10.1037/0022-3514.66.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic processing can bias systematic processing: Effects of source credibility, argument ambiguity, and task importance on attitude judgment.

Abstract: High- and low-task-importance Ss read a strong or weak unambiguous message or an ambiguous message that was attributed to a high- or low-credibility source. Under low task importance, heuristic processing of the credibility cue was the sole determinant of Ss' attitudes, regardless of argument ambiguity or strength. When task importance was high and message content was unambiguous, systematic processing alone determined attitudes when this content contradicted the validity of the credibility heuristic; when mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

65
956
10
16

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,113 publications
(1,071 citation statements)
references
References 39 publications
(89 reference statements)
65
956
10
16
Order By: Relevance
“…Importantly, further analyses revealed that the attitudinal impact of this heuristic was mediated in part by more effortful processing. Just as other heuristic cues in the service of other motives have been shown to bias subsequent processing (Chaiken & Maheswaran, 1994), impression-motivated participants' heuristic processing of the partner attitude information biased the evaluative nature of their systematic processing in a direction consistent with their partners' opinions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, further analyses revealed that the attitudinal impact of this heuristic was mediated in part by more effortful processing. Just as other heuristic cues in the service of other motives have been shown to bias subsequent processing (Chaiken & Maheswaran, 1994), impression-motivated participants' heuristic processing of the partner attitude information biased the evaluative nature of their systematic processing in a direction consistent with their partners' opinions.…”
Section: Discussionmentioning
confidence: 99%
“…Although heuristic and systematic processing may occur alone, they may also co-occur in particular ways (Chaiken et al, 1989). For example, the evaluative implication of a heuristic cue may bias the nature of systematic processing (Chaiken & Maheswaran, 1994). To illustrate, favorable consensus cue information may lead our consumer to interpret ambiguous information about the automobile more favorably, because the consensus cue establishes the expectation of encountering positive information about the car.…”
Section: The Heuristic-systematic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Para minimizar esse tempo, o consumidor utiliza atalhos na tomada de decisão, tornandoa mais heurística (Chaiken & Maheswaran, 1994). Neste caso, o constrangimento serve como um limitador de recursos de processamento de informação, uma vez que tanto expressar quanto suprimir emoções resultam num aumento de carga cognitiva (Bonanno, Papa, Lalande, Westphal, & Coifman, 2004).…”
Section: Fugirunclassified
“…We will examine how consumers perceive, assess and process label information. The three determined factors "Attributes of bio-based plastics", "Environment and examination" and "Renewable resources" will be used in the context of the Heuristic-Systematic Model (Chaiken & Trope, 1999;Chaiken & Maheswaran, 1994;Eagly & Chaiken, 1993).…”
mentioning
confidence: 99%